2015
DOI: 10.1245/s10434-015-4410-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Computed Tomography for Preoperative Staging of Patients with Non-endometrioid Carcinomas of the Uterine Corpus

Abstract: Purpose The aim of this study was to assess the diagnostic performance of computed tomography (CT) for initial staging of non-endometrioid carcinomas of the uterine corpus. Materials and Methods Waiving informed consent, the Institutional Review Board approved this Health Insurance Portability and Accountability Act (HIPAA)-compliant retrospective study of 193 women with uterine papillary serous carcinomas, clear cell carcinomas, and carcinosarcomas, who underwent surgical staging between May 1998 and Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Currently, in addition to serving as a fluorophoric agent for use in diagnostic purposes such as NIR image-guided oncologic surgery [14], fluorescence angiography [15], and lymph node detection of cancer [16], ICG has been exploited as a photosensitizer for use in cancerous phototherapy including breast, brain, and skin tumors [1719] since it enables to produce heat and ROS (i.e., singlet oxygen) upon NIR irradiation. Although ICG is of particular advantage for use in cancer phototherapy, it adversely tends to disintegrate in aqueous medium and such degradation can be markedly accelerated by light irradiation (photodegradation) and/or heating (thermal degradation) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, in addition to serving as a fluorophoric agent for use in diagnostic purposes such as NIR image-guided oncologic surgery [14], fluorescence angiography [15], and lymph node detection of cancer [16], ICG has been exploited as a photosensitizer for use in cancerous phototherapy including breast, brain, and skin tumors [1719] since it enables to produce heat and ROS (i.e., singlet oxygen) upon NIR irradiation. Although ICG is of particular advantage for use in cancer phototherapy, it adversely tends to disintegrate in aqueous medium and such degradation can be markedly accelerated by light irradiation (photodegradation) and/or heating (thermal degradation) [20].…”
Section: Introductionmentioning
confidence: 99%
“…Neoplastic pathologies can not benefit from a correct and effective therapeutic attitude in the absence of imaging. Initially, when there is suspicion of a pelvic tumor on the basis of patient's symptoms and bio-humoral investigations, it is recommended to perform a thoraco-abdomino-pelvic computerized tomographic scan with contrast agent to assess the location, size and consistency tumor, relationships with surrounding tissues, or distant extension [14]. Magnetic Resonance and PET-CT are imaging investigations that add extra features to describing neoplasia.…”
Section: Resultsmentioning
confidence: 99%
“…In comparative studies of CT with US or MRI for myometrial invasion, the accuracy of CT is reported to be 58% to 61% versus 68% to 69% for US and 88% to 89% for MRI. 21,22 In select cases, CT chest and abdomen is indicated as a part of metastatic workup.…”
Section: Diagnosis and Stagingmentioning
confidence: 99%